The Effect of Soybean Meal Subtitution with leaves turi (Selsabania grandiflora) fermented in Artificial feed on growth of Fish Seed Baung (Selsabania grandiflora) - Simangunsong, Gidion; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in the experimental pond from Juny to August 2016 in the Nutrition Fish Laboratory, Fisheries and Marine Science, University of Riau, Pekanbaru. The purpose of this study to determine the concentration of leaves turi fermented flour in fish feed formulation Baung (Hemibagrus nemurus), and also to know the response for feed using to digestibility, feed efficiency and on growth Baung (Hemibagrus nemurus). The method of this research is Experiment method uses a completely randomized design (RAL) with one factor, the level 5 treatments and 3 replications with the result that needing 15 experiment units.The feed used artificial feed with the content of leaves turi fermented and different percentage are P0 (0%), P1 (5%), P2 (10%), P3 (15%), P4 (20%).The results showed that the highest treatment contained in P2 (leaves turi fermented) represented digestibility 75,25%, the feed efficiency of 48,76%, retention of protein 16,70%, specific growth rate of 3,22 % and survival rate of 98,33%. This means that leaves turi fermented flour as one of alternative substance of feed for replacement soybean flour.Keywords : Hemibagrus nemurus, Leaves turi, Fermentation